Studi Eksperimental Unjuk Kerja Campuran Solar-Biodiesel Minyak Jelantah Pada Mesin Diesel - Ade Setiawan; Joko Winarno; Mochamad Syamsiro (Universitas Janabadra, 2017)
In this study, biodiesel fuel produced from waste cooking oil was blended in 20%, 30%, 40% and 50% with the commercial diesel fuel. The biodiesel was collected from a company near Yogyakarta city. It was produced from transesterification process in a commercial scale reactor. The diesel-biodiesel mixtures were tested in a four-cylinder and four-stroke diesel engine with the compression ratio of 18 and water cooling system. The results show that the thermal efficiency of diesel engine increased with increasing the engine speed. The present of biodiesel also increased the thermal efficiency of the diesel engine. A mixture of 40% (B40) and 50% (B50) biodiesel resulted in the highest thermal efficiency. The brake mean effective pressure also increased with increasing the engine speed and biodiesel mixture. The specific fuel consumption showed a decrease in its value as a function of engine speed. Low specific fuel consumption means the high thermal efficiency of the diesel engine.